Rethinking strategy and implementation of knowledge management from innovation perspective: A lesson learned from a multinational subsidiary in Indonesia - Mirta Amalia; Yanuar Nugroho (The University of Manchester, Manchester Business School, 2010)
Facing unprecedented challenges and opportunities ahead in the knowledge economy, managing knowledge has been a priority for many organisations. Knowledge Management (KM) emerges and has quickly gained weight in research both from information systems perspective and management sciences. An amply documented dilemma is the absence of specific implementation guide due to different organisation's characteristics and strategies. At times, endeavours to integrate KM into the organisation's strategy and to customise it to meet organisation's characteristics instead create undesired problems because of its prioritisation. We explore the implementation of KM in a telecommunication multinational subsidiary in Indonesia and investigate factors that affect the performance as well as the impacts. Benefiting from innovation perspective we identify the way KM strategies are devised and put into action. Using in-depth interviews and direct observation, we map some problems associated with the strategy and implementation of KM. We learn in our case that the lack of organisation-wide integrated systems, which is typical across different organisations, does contribute to this problem. However the main predicament lies on the fact that KM enabling scheme is never explicitly prioritised in the organisation's information systems strategy.
Keywords: 330; knowledge management; information systems; strategy; knowledge transfer